Ջուղայի տարազը (18–20-րդ դդ. ) - Մալխասյան, Քնքուշ (Հայաստանի պատմության թանգարան)
The article represents the description of the folk costume of New Julfa, the preconditions for its formation. A brief historical overview shows the destruction of Old Julfa and the history of the creation and construction of New Julfa. The article categorizes the men’s and women’s clothing collections of New Julfa with a sequential and detailed description. В статье представлено описание Национального костюма Новой Джуги, предпосылки ее формирования. Краткий исторический обзор показывает разрушение Старой Джуги и историю создания и строительства Новой Джуги. В статье классифицированы коллекции мужской и женской одежды Новой Джуги с его последовательным и подробным описанием.
Keywords: Ազգագրություն